Kaka Baptista Gardens on Mazagaon Hill - Mumbai Archive Project Team (Jio Institute, 2024)
Kaka Baptista Gardens on Mazagaon Hill is named after Joseph ‘Kaka’ Baptista, who was born in Matharpacady in 1861. In 1925, he was elected as the mayor of the Bombay Municipal Corporation. A barrister by qualification, he practised law at the Bombay High Court. He was also involved in politics and advocated for the rights of the East Indian community. Bal Gangadhar Tilak and Kaka Baptista were close allies during the Indian Home Rule Movement.